Hypnotizability-Related Effects of Pain Expectation on the Later Modulation of Cortical Connectivity. Issue 3 (2nd July 2020) - Zarei, Seyedeh-Parisa; Briscese, Lucia; Capitani, Simone; Rossi, Bruno; Carboncini, Maria C.; Santarcangelo, Enrica L.; Motie Nasrabadi, Ali
ABSTRACT: This study examined hypnotizability-related modulation of the cortical network following expected and nonexpected nociceptive stimulation. The electroencephalogram (EEG) was recorded in 9 high ( highs ) and 8 low ( lows ) hypnotizable participants receiving nociceptive stimulation with (W1) and without (noW) a visual warning preceding the stimulation by 1 second. W1 and noW were compared to baseline conditions to assess the presence of any later effect and between each other to assess the effects of expectation. The studied EEG variables measured local and global features of the cortical connectivity. With respect to lows, highs exhibited scarce differences between experimental conditions. The hypnotizability-related differences in the later processing of nociceptive information could be relevant to the development of pain-related individual traits. Present findings suggest a lower impact of nociceptive stimulation in highs than in lows.